Hesperopenna gilolo sp. nov., the easternmost record of the genus from Halmahera, Indonesia (Coleoptera: Chrysomelidae: Galerucinae) - Bezděk, Jan (Zootaxa, 2023)
Hesperopenna gilolo Bezdĕk, sp. nov. from Halmahera (Indonesia), characterized by black elytra and the peculiar shape of the median lobe of the aedeagus, is described. Color photos of the habitus, body details, and drawings of the penis are presented. The new species represents the easternmost record of the genus Hesperopenna Medvedev & Dang, 1981 and the first record of the genus in the Wallacea and Maluku archipelago.